2018
DOI: 10.14715/cmb/2018.64.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and somatic embryogenesis in Stevia rebaudiana Bertoni as a medicinal plant

Abstract: Stevia rebaudiana (Bert.) from Asteraceae family is a useful medicinal plant that prevents and cures diabetes, blood pressure, weight gain and tooth decay. Due to self-incompatibility in stevia, somatic embryo investigation for artificial seed production is valuable in this plant. In order to evaluate the callus induction characteristics in stevia, a factorial experiment was laid out based on a completely randomized design with three replications. The factors included ten hormone combinations and control, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
5
5
0
Order By: Relevance
“…In our study, the calli started to appear 10 days after the induction treatment, with varying sizes, color, consistency and morphogenesis. The results observed in this study corroborate the findings for Stevia rebaudiana Bertoni, where the time of callus induction was six days using 1 mg L -1 BAP + 1 mg L -1 NAA for both media (MS and B5) and explant types (leaf and internode) (Keshvari et al, 2018). On the other hand, other authors have reported no significant difference between interaction effects of explant type × hormone concentration on callus induction percentage in Cuminum cyminum L. (Kazemi; and Mentha pulegium L. (Jafari;.…”
Section: Embryogenic Callus Induction and Multiplication Of Leaf And supporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the calli started to appear 10 days after the induction treatment, with varying sizes, color, consistency and morphogenesis. The results observed in this study corroborate the findings for Stevia rebaudiana Bertoni, where the time of callus induction was six days using 1 mg L -1 BAP + 1 mg L -1 NAA for both media (MS and B5) and explant types (leaf and internode) (Keshvari et al, 2018). On the other hand, other authors have reported no significant difference between interaction effects of explant type × hormone concentration on callus induction percentage in Cuminum cyminum L. (Kazemi; and Mentha pulegium L. (Jafari;.…”
Section: Embryogenic Callus Induction and Multiplication Of Leaf And supporting
confidence: 89%
“…Observations from other authors indicate that the type of medium and explant are important factors in quantity and quality of calli obtained from explants (Keshvari et al, 2018). Kumlaya and Ercisli, (2015) also noted that the callus induction percentage and friability of the produced calli varied widely between explants.…”
Section: Callus Oxidationmentioning
confidence: 94%
“…Phytohormones are another key influencing factors for SE. Most plant species undergoing SE are dependent on the powerful action of auxin and cytokinin, especially 2,4dichlorophenoxyacetic acid (2,4-D) which regulates and balances endogenous auxin levels (Illyas Ahmad et al, 2013;Mahendran and Bai, 2016;Keshvari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in vitro culture of callus has been reported as an alternative method for the production of biomass aiming at the production of secondary metabolites, especially for the ease of induction and proliferation, being a simpler process than organogenic or embryogenic responses, which allows increasing the in vitro plant biomass, one of the main economic limitations in the production of secondary metabolites in vitro [ 8 ]. In addition, the induction and proliferation of calli in vitro allow good repeatability and standardization of responses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%